Impact of water on peak and residual shear strength parameters and triaxial deformability of high-porosity building calcarenite stones: Interconnection with their physical and petrological characteristics. (30th November 2020) - Rabat, Á.; Tomás, R.; Cano, M.; Miranda, T.
Highlights: Triaxial compressive strength and deformability of dry and wet calcarenite stones. Mohr-Coulomb and Hoek-Brown failure envelopes were generated for calcarenites. Peak and residual compressive strength and Young modulus decrease due to water. Water induces important variations on peak and residual shear strength parameters. Water-weakening effect might be caused by some physicochemical processes. Abstract: Several studies have found that water can cause substantial reductions of mechanical properties of building stones such as unconfined compressive strength, tangent Young's modulus or tensile strength. However, the influence of water content on shear strength parameters, triaxial compressive strength and modulus of elasticity under different confining pressures has been scarcely examined. For this reason, the present paper assesses the impact of water on peak and residual compressive strength and tangent Young's modulus of three porous building geomaterials widely used in civil and architectural constructions under different confining pressure through triaxial compressive tests. Furthermore, the corresponding peak and residual shear strength parameters computed from Mohr-Coulomb ( c and ϕ ) and from Hoek-Brown ( σ ci and m i ) failure criteria are obtained under dry and saturated conditions. Complementary physical and petrological analyses are performed in order to understand the main causes of the effect of water observed in these rock materials. The results indicate that water causes significant reductions of peak and residual compressive strength and tangent Young's modulus in the tested porous building stones for all the different applied confining pressures. Additionally, important changes of peak and residual shear strength parameters ( c, ϕ, σ ci and m i ) are exhibited by the studied stones when become saturated. This could be related to physicochemical changes such as the hydrolysis of quartz and silicates in crack tip region inducing subcritical crack growth (stress corrosion), the decrease of the cement quality and the deterioration of the intergranular bonds due to the dispersion or dissolution of some minerals (calcite or chlorite) and the formation of microcracks caused by the swelling of the clay minerals present in these materials when they come into contact with water.